HISTORY OF THE DEVELOPMENT OF THE MOSQUE AS AN ISLAMIC EDUCATIONAL INSTITUTION - Indah Suryani; Tamsik Udin; Kisno (Mandeh : Jurnal Pendidikan Islam, 2026)
Mosques have a significant historical role in the development of Islamic education in Indonesia, not only as places of worship but also as centers of learning and community development. Along with social change and the development of the modern education system, the function of mosques as educational institutions faces various challenges that require strengthening and adapting their role. Based on this background, this study aims to analyze the historical development of mosques as Islamic educational institutions in Indonesia and understand their role and impact on the education system. This study uses a qualitative approach with a literature study method, through data collection from books, scientific journal articles, and relevant previous research results. The results show that mosques function not only as places of worship but also as educational centers that teach the Qur'an, fiqh, and life skills to the community. In the modern era, the strategic role of mosques allows the community to obtain formal and non-formal education relevant to the needs of the times. The implications of this study emphasize the importance of increasing support for mosques as educational institutions through the development of an integrated curriculum and improving the quality of teaching resources. Thus, mosques are expected to continue to contribute to advancing education and the moral development of the Muslim community in Indonesia.